Pomegranate extract (Punica granatum) not as effective as simvastatin in improving profile lipid in dyslipidemic male wistar rats (Rattus norvegicus) - Ken Andrina Anindita; I Gusti Made Aman; Gde Ngurah Indraguna Pinatih (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Dyslipidemia is one of the factors of the occurrence of heart disease and atherosclerosis. Simvastatin and Pomegranate (Punica granatum) work by improving the lipid profile. The aim of this study was to prove that red pomegranate extract (Punica granatum) improve lipid profile of male white rats that are dyslipidemic. Method: This research is a experimental study with randomized pre test and post test control group design, using 20 adult male white rats as sample. After 30 days, rats were divided into 2 study groups with 10 rats per group. The group was classified into two (P1 and P2). Prior to the treatment, the rats were examined the first diluted T-cholesterol, triglyceride, LDL and HDL levels as pretest data. Treatment was performed for 15 days. Results: The mean pretest HDL level in the simvastatin group was 23.84 ± 2.54 mg / dL and the red pomegranate extract group was 25.41 ± 2.34 mg / dL and p = 0.167. After treatment for 15 days, the mean posttest the red pomegranate extract group was 126.55 ± 3.09 mg / dL and p = 0,001. The mean posttest HDL level in the simvastatin group was 58.72 ± 5.21 mg / dL and the red pomegranate extract group was 40.56 ± 2.87 mg / dL and p = 0,001. Conclusion: The administration of red Punica granatum is not as effective as simvastatin in improving lipid profile in dyslipidemic rats. Although not as effective as simvastatin, red pomegranate extract can significantly improve lipid profile.